Fatores de risco para infecção da corrente sanguínea e mortalidade por Staphylococcus aureus resistente à oxacilina - Bakowski, Elcio [UNIFESP] (2006)
Objectives: The objective of this study was to evaluate the incidence of infection and the risk factors associated to bacteraemia and mortality due to methicillin -resistant Staphylococcus aureus (MRSA). Methods: This cohort study, conducted from August 2004 through November 2005, involved 60 consecutively identified patients with bloodstream MRSA infection. The control group included 240 non-infected patients, randomly selected and hospitalized on the day, or immediately after, results of blood culture of case patients were available. A case-control (1:4) study was conducted for evaluation of risk factors for bacteraemia and death. Results and conclusions: The incidence of infection was 1.99/1000 admissions. Mortality rates were 30% among patients and 5.38% among controls, with an attributed death rate of 24.6%. Multivariate analysis indicated the following risk factors for bacteraemia: severity of the underlying disease (OR=3.3; 95% CI: 1.13- 9.66), use of central venous catheter (OR=15; 95% CI: 6.82-34.71), and use of corticoids (OR=2.3; 95% CI: 1.13-4.97). The univariate analysis of risk factors for mortality did not show, among the parameters investigated, predictors of mortality unique to MRSA. When the 300 patients were combined, however, multivariate analysis showed a more severe clinical score for patient’s underlying disease (OR=9.6; 95% CI: 1.12-83.37), use of mechanical ventilation (OR=15.5; 95% CI: 3.86-62.72) and use of corticoids (OR=6.6; 95% CI: 2.19-19.98).